Survival and risk factors associated with surgical repair of ventricular septal rupture after acute myocardial infarction: A single-center experience - Zhao, Keyan; Li, Baoyin; Sun, Biao; Tao, Dengshun; Jiang, Hui; Wang, Huishan (Frontiers in Cardiovascular Medicine, 2022)
Objective: To analyze the survival and risk factors associated with the surgical treatment of ventricular septal rupture (VSR) after acute myocardial infarction (AMI). Methods: We retrospectively analyzed 45 consecutive patients with VSR after AMI whose procedures were performed between January 2012 and December 2021. Patients were divided into two groups: the survival group and the death group. The Kaplan–Meier method and log-rank test were used to determine the cumulative incidence of all-cause mortality. Multivariate logistic regression was used to evaluate the independent risk factors for all-cause mortality. Results: The average postoperative follow-up time was 42.1±34.1 months. The overall mortality rate was 20% (9/45 patients) and the operative mortality rate was 8.9% (4/45 patients). A logistic analysis showed that the death group had higher serum creatinine (127.32±47.82 vs. 82.61±27.80 μmol/L, respectively; P=0.0238) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) [8654.00 pg/mL (6197.00–11949.00 pg/mL) vs. 4268.96 pg/mL (1800.00–7894.00 pg/mL), respectively; P=0.0134] levels than the survival group. The cardiopulmonary bypass time was longer in the death group than in the survival group [131.00 min (121.00–184.00 min) vs. 119.00 min (103.00–151.50 min), respectively; P=0.0454]. Significantly more red blood cells were transfused in the death group than in the survival group [11.60 units (6.10–16.50) vs. 3.75 units (0.00–7.00 units), respectively; P=0.0025]. Intra-aortic balloon pump implantation (p=0.016) and ventilation time (p=0.0022) were risk factors for mortality. A 1-month landmark analysis showed that compared with patients with VSR to surgical time > 14 days, patients who underwent surgery within 14 days had a higher rate of all-cause mortality (25.00% vs. 3.33%; log-rank P=0.023). Patients with VSR within 14 days also had a higher rate of more than moderate residual shunts. Multivariate analysis showed that the transfusion of red blood cells and the NT-proBNP level were risk factors for all-cause mortality and major adverse cardiovascular and cerebrovascular events. Conclusions: Surgical repair resulted in good outcomes for patients with VSR after AMI. Patients with VSR to surgical time >14 days had a lower rate of all-cause mortality. Treatment strategies for VSR should be based on the patient’s condition and comprehensively determined through real-time evaluation and monitoring.